2016
DOI: 10.1149/2.0051609jes
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Performance Improvement of Graphite Electrode by Allyl Sulfide Additive and Its Film-Forming Mechanism

Abstract: This work describes the beneficial effects given by the allyl sulfide (AS)-derived surface film on the low-temperature performances of graphite electrode and the film-forming mechanism. Adding a small amount of allyl sulfide as an electrolyte additive into a Li/graphite cell increases the reversible capacity of graphite electrode to three times larger than that of the AS-free cell at −30 • C. Lithium plating is also suppressed by adding AS into the background electrolyte. An impedance analysis reveals that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…[124] Holoubek et al [15] designed the electrolyte of 1 m LiPF 6 with a mixture of methyl 3,3,3-trifluoropionate (MTFP)/FEC (9:1 by vol) for ultralowtemperature application of LMBs (Figure 8b). The synergistic effect of MTFP with excellent oxidative stability (≈5.8 V) and Jurng et al [102] 0.5 wt% DMS 1.0 m LiPF 6 EC/EMC (1:2, wt)…”
Section: Low-temperature Organic Electrolytes For High-energy Battery...mentioning
confidence: 93%
See 1 more Smart Citation
“…[124] Holoubek et al [15] designed the electrolyte of 1 m LiPF 6 with a mixture of methyl 3,3,3-trifluoropionate (MTFP)/FEC (9:1 by vol) for ultralowtemperature application of LMBs (Figure 8b). The synergistic effect of MTFP with excellent oxidative stability (≈5.8 V) and Jurng et al [102] 0.5 wt% DMS 1.0 m LiPF 6 EC/EMC (1:2, wt)…”
Section: Low-temperature Organic Electrolytes For High-energy Battery...mentioning
confidence: 93%
“…[96][97][98][99][100][101] Allyl sulfide (AS)-added electrolytes were demonstrated to be spontaneously decomposed on the surface of soaked graphite and form a sulfur-containing inner layer SEI, which facilitated the charge-transfer process at low temperatures. [102] Besides, the addition of 2 wt% AS could also suppress Li plating, further enhancing the low-temperature performance of cells. Guo et al [103] reported that the graphite||NCM523 pouch cells with carbonate electrolyte (1 m LiPF 6 EC/EMC, 1:2 by wt) containing 0.5 wt% DMS exhibited superior low-temperature performance, outperforming the commercialized DTD additive (Figure 7a).…”
Section: Additives For Organic Low-temperature Electrolytesmentioning
confidence: 99%
“…[ 12 ] The SEI film has generally been recognized as the most resistive component in the journey of the Li‐ion transportation. [ 13 ] An increased R ct can be observed as the temperature decreased below zero, indicating the sluggish charge transportation on SEI. [ 14 ] The interfacial and bulk impedances rapidly increased with the decrease of temperature.…”
Section: Fundamental and Challenge In Electrolyte Designmentioning
confidence: 99%
“…Some sulfite solvents with high dielectric constant and wide temperature range show excellent compatibility with SiO/C anode, which are usually used as additives of electrolytes to promote the formation of SEI and produce sulfide with low impedance. [26][27][28][29][30][31] However, the oxidation of sulfur-containing solvent at higher potential leads to its continuous consumption and limits its further application in full batteries. [32] In addition, the structure and performance-dependent properties of SEI layer has not been clearly demonstrated which also impede its rational design and optimization.…”
Section: Introductionmentioning
confidence: 99%